Development and psychometric evaluation of the Spanish Cooking Self-Efficacy Questionnaire (SCSEQ) for Spanish University Students - Patricia Jurado-Gonzalez; F. Xavier Medina; Alba Martínez-Garcia; Almudena López-Cediel Verdú; Sergi Fàbregues; Anna Bach-Faig (PLoS ONE, 2026)
The transition to university is a critical life stage characterized by increased autonomy, identity exploration, and new social and environmental influences. During this period, university students often exhibit low adherence to dietary guidelines. Among the determinants influencing healthy eating, cooking self-efficacy, the central construct of Social Cognitive Theory (SCT), is consistently associated with improved diet quality and is a frequent target of health interventions. However, no validated instrument exists to assess this construct among university students in Spain. Therefore, the goal was to develop and provide preliminary evidence of the Spanish Cooking Self-Efficacy Questionnaire (SCSEQ), a concise SCT-based instrument tailored to Mediterranean university settings. A 32-item questionnaire was developed through a review of existing instruments assessing cooking self-efficacy. Face validity was evaluated with Spanish food and nutrition experts (n = 12) to assess the clarity and pertinence of the initial items. The revised Spanish Cooking Self-Efficacy Questionnaire (SCSEQ) was then pilot-tested with Spanish university students (n = 73) from four Catalan universities. Exploratory factor analysis (EFA) was conducted to identify the underlying factor structure and detect problematic items. Internal consistency reliability was assessed using McDonald’s ω, and test–retest reliability over a two-week interval was evaluated using Pearson correlations. Face validity indicated overall clarity and adequacy. Four items were excluded and recombined, two items were added, and nine items were rewritten based on experts’ feedback. After pilot testing, the questionnaire overall demonstrated high internal consistency (ω = 0.9). Items were reviewed based on factor loadings, item redundancy, theoretical relevance, and their contribution to scale-level internal consistency. EFA suggested a two-factor structure with good internal consistency (ω = 0.88 and ω = 0.82) and test–retest reliability (ICC = 0.91, 95% CI [0.80, 0.96]). Three items with weak loadings were excluded. The final version consisted of 25 items and 2 subscales. The SCSEQ showed favorable preliminary psychometric properties.